Tragedi Kematian Tuhan: Kajian atas Aforisme Nietzsche “Tuhan Telah Mati” - Muhammad Anwar Firdausi (UIN Maulana Malik Ibrahim Malang, 2004)
The declaration of “God is dead” is the most memorable statement for people knowing Nietzsche. That declaration made him well-known around the world for centuries. It is no wonder that he then got people’s negative impression, for example “The God’s butcher” which is identical to atheism and other anti-religion communities. At a glance, Nietzsche is seen as the hater of God though wisely he deserved to be in the mid position between “religion and anti-religion” or “religious and secular”. The reason is that, The God he hates is The One being arbitrary and unfair. He wants others to be free from the fake promises of the world and search for the truth. Proklamasi God is dead adalah pernyataan yang paling melekat dalam ingatan orang tentang sosok Nietzsche. Sabda itulah yang melambungkan dirinya hingga pada tingkat kesohoran melintasi ruang geografis dan waktu dalam hitungan abad. Tidak heran jika kemudian ia mendapatkan beragam stigma. Sebut saja julukan “Sang Penjagal Tuhan” yang diidentikkan dengan ateisme dan gerakan-gerakan anti agama. Sekilas Nietzsche terlihat seperti pembenci Tuhan meskipun secara bijak ia telah pantas berada pada posisi tengah di antara “agama dan anti agama”, “religius dan sekular”. Alasannya ialah Tuhan yang dia benci adalah Tuhan yang sewenang-wenang dan tidak adil. Ia ingin agar manusia bebas dari janji-janji palsu dunia dan mulai mencari kebenaran.